Penerapan Metode Giving Question and Getting Answer untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Azis, Abdul; Zali, Muhammad; Indriani, Fatma; Lubis, Masruroh (Fitrah: Journal of Islamic Education, 2023)
Mistakes in choosing learning methods have an impact on learning outcomes. So in that case the teacher must be able to determine the appropriate learning method. This study aims to improve student learning outcomes in the Islamic Religious Education subject by applying the Giving Question and Getting Answer learning method. The focus of this research is on two things, namely improving post-action learning outcomes and student learning activities. This research was conducted on class XI students of Madrasah Aliyah, Laboratory of UIN Sumatra Utara Medan. This study used the Classroom Action Research method, which was carried out in three cycles. Collecting data using observation, tests, and interviews. The results of this study indicate that the learning outcomes of students in cycle I got an average score of 76.34 in the calculation of 27 people who had completed and 3 people who had not completed the KKM score that had been determined, cycle II with an average score of 86.66 in the calculation of 28 people has been completed and 2 people have not completed the specified KKM value, cycle III with an average value of 95.12 in the calculation of 29 people has been completed and 1 person has not completed the specified KKM value. This research succeeded in proving the allegation that the giving question and getting answar methods can help improve learning outcomes.